2014
DOI: 10.1161/circresaha.114.302437
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice for Real-Time Visualization of cGMP in Intact Adult Cardiomyocytes

Abstract: 1235 3ʹ,5ʹ-Cyclic guanosine monophosphate (cGMP) is one of the ubiquitous second messengers, which is critically involved in the regulation of cardiac contractility and pathological hypertrophy.1,2 In cardiomyocytes, 2 classes of guanylyl cyclases (GCs) are responsible for cGMP synthesis. The first class, particulate GCs (pGCs) represented by GC-A and GC-B, are plasma membrane receptors for atrial natriuretic peptide (ANP) and C-type natriuretic peptide (CNP), respectively. 3,4 Second, the so-called soluble or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 49 publications
8
70
1
Order By: Relevance
“…Adult ventricular cardiomyocytes were isolated via the Langendorff perfusion 18,38 . Mice were euthanized and the hearts were quickly transferred into a chamber filled with ice-cold PBS (Biochrom) where the aorta was connected to a 21G cannula.…”
Section: Methodsmentioning
confidence: 99%
“…Adult ventricular cardiomyocytes were isolated via the Langendorff perfusion 18,38 . Mice were euthanized and the hearts were quickly transferred into a chamber filled with ice-cold PBS (Biochrom) where the aorta was connected to a 21G cannula.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that cardiac cGMP can affects cardiac properties by modulating cAMP levels, bypassing again cGKI (16,17). Thus, the site(s) of action of cGMP/cGKI are not entirely clear (18) and interpretation of cGMP/cGKI effects on cardiac hypertrophy may be quite complicated.…”
mentioning
confidence: 99%
“…Using a genetically encoded cGMP FRET-based sensor in intact adult CMs (Götz et al, 2014), we observed that CNP induced an ∼2-fold-higher cGMP elevation in AT 1 R tg/1 cells (isolated from 120-day-old double-transgenic mice) compared with control mice that carried only the FRET-based sensor (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze CM-specific changes in cGMP levels, we crossed aMHC-AT 1 R tg/1 animals with red cGES-DE5 transgenic cGMP sensor mice (Götz et al, 2014). Adult CMs were isolated from double-transgenic animals versus littermate controls expressing the sensor without AT 1 R overexpression and subjected to cGMP-Förster resonance energy transfer (FRET) measurements under stimulation with C-type natriuretic peptide (CNP) (1 mM) and 3-isobutyl-1-methylxanthine (IBMX) (100 mM) as previously described (Götz et al, 2014).…”
Section: Methodsmentioning
confidence: 99%